Monitoring CO2 injection into a saline aquifer: Otway Project feasibility study - Pevzner, Roman; Galvin, R.; Madadi, Mahyar; Urosevic, Milovan; Caspari, Eva; Gurevich, Boris; Lumley, D.; Shulakova, V.; Cinar, Y.; Tcheverda, V. (SEG, 2012)
A key objective of Stage 2 of the CO2CRC Otway Project is to explore the ability of geophysical methods to detect and monitor injection of greenhouse gas into a saline formation. For this purpose, injection of some 10,000 – 30,000 t of gas mixture (80/20% CO2/CH4 by mole fraction in the supercritical state) into the Paaratte formation, a saline aquifer located at a depth of about 1,400 m is planned. Before such an injection experiment is undertaken, we assess the feasibility of geophysical monitoring using computer modeling. To examine the detectability of the plume we need to estimate the time-lapse signal and time-lapse noise. The time lapse signal is modeled using flow simulations, fluid substitution and seismic forward modeling. The level of time lapse noise is estimated from existing time-lapse 3D data in the area. The results confirm that the plume stemming from the injection of 10,000 t of CO2 / CH4 will probably be detectable, and that an increase of the injection volume to 30,000 t will give a significantly higher confidence of the plume detection.